Microstructural evolution and strengthening mechanism of high-strength AlSi8.1 Mg1.4 alloy produced by selective laser melting. (June 2022) - Geng, Yaoxiang; Wang, Qing; Wang, Yingmin; Zang, Qianhao; Mi, Shaobo; Xu, Junhua; Xiao, Yakai; Wu, Yi; Luan, Junhua
Graphical abstract: Highlights: A high-strength AlSi8.1 Mg1.4 aluminum alloy was specifically designed for SLM. GP zones/Mg-Si clusters were formed in as-built alloy. After direct aging, β ″ nanoparticles were precipitated from α -Al cells. The strength of present alloy was much higher than that of SLM AlSi10Mg alloys. Abstract: A high-strength AlSi8.1Mg1.4 aluminum alloy was specifically designed for selective laser melting (SLM) by doubling the Mg content of A357 alloy based on the rapid solidification characteristics of the SLM process. The alloy showed good processability with maximum density over casting alloy with the same composition. The microstructure of the as-built alloy was characterized by the formation of cell structure. The α -Al cells manifested GP zones/Mg-Si clusters. The yield strength (YS), ultimate tensile strength (UTS), and elongation to fracture of the as-built alloy were 341 ± 14 MPa, 518 ± 6 MPa, and 7.1 ± 0.4%, respectively. Due to the precipitation of β ″ nanoparticles in α -Al cells, the strength of the SLM alloy was effectively improved after direct aging at 150 ℃ and 200 ℃, with a maximum YS of 446 ± 5 MPa and maximum UTS of 546 ± 1 MPa, which were much higher than those of Al-Si-based alloy produced by SLM. When the aging temperature exceeded 200 ℃, the strength of the alloys decreased rapidly, but the elongation increased significantly. Multiple strengthening mechanisms, including grain refinement, GP zones/Mg-Si clusters, and β ″ nanoparticle precipitation contributed to the high strength of SLM AlSi8.1Mg1.4 alloy.